AB0480 Certolizumab pegol plus methotrexate is similarly effective in active rheumatoid arthritis regardless of prior TNF inhibitor use: Analysis of the doseflex PHASE IIIB study. (23rd January 2014) - Schiff, M.; Davies, O.; Bennett, B.; Luijtens, K.; Furst, D.E.
Abstract : Background: Certolizumab pegol (CZP) was associated with a rapid, consistent clinical response in a diverse group of RA patients (pts), including those with prior TNF inhibitor exposure. 1 Objectives: To investigate the efficacy of CZP in pts with active RA with and without prior TNF inhibitor exposure in the DOSEFLEX dose comparison trial. Methods: DOSEFLEX was a 34 week (Wk) Phase IIIb, open-label run-in and double-blind placebo (PBO)-controlled randomized study in pts with active RA on stable dose MTX (NCT00580840 ). Primary TNF inhibitor non-responders were excluded. During the run-in period, all pts received 400 mg CZP at Wks 0, 2, and 4, and 200 mg CZP every 2 Wks (Q2W) to Wk 16 (+ MTX). ACR20 responders at Wk 16 were randomized 1:1:1 at Wk 18 to receive 200 mg CZP Q2W + MTX, 400 mg CZP Q4W + MTX or PBO + MTX for a further treatment period of 16 Wks. The primary end-point of the trial was ACR20 response at Wk 34; ACR responses and CDAI/SDAI/DAS28(ESR) remission were assessed using NRI, and DAS28(ESR) change from baseline using LOCF for missing data imputation. Results: Of 333 pts who entered the run-in, 53.5% had prior TNF inhibitor use. Mean DAS28(ESR), SDAI and CDAI at baseline were 6.4, 40.4 and 38.4, respectively. At Wk 16, the responder rates for pts with and without prior TNF inhibitor exposure were; ACR20, 60.7% vs. 61.9%; ACR50, 34.8% vs. 41.3% and ACR70, 14.0% vs. 18.7%. Clinical remission at Wk 16 was 14.6% vs. 19.4% for DAS28(ESR), 12.9% vs. 15.5% for SDAI and 14.0% vs. 16.8% for CDAI. Of the pts with an ACR20 response at Wk 16 who were randomized at Wk 18, 61.4%, 55.7% and 42.0% had prior TNF inhibitor use in the CZP 200 mg, CZP 400 mg and PBO groups, respectively. Mean baseline characteristics for all randomized pts with and without prior TNF inhibitor exposure were: DAS28(ESR), 6.3 and 6.4, SDAI: 39.4 and 40.0, CDAI: 37.5 and 38.0. In Wk 16 responders, ACR20 response rates at Wk34 in pts with vs. without prior TNF exposure were 74.4% vs. 55.6% in the 200 mg CZP group, 61.5% vs. 70.0% in the 400 mg CZP group and 37.9% vs. 50.0% in the PBO group. ACR50 (Fig.) and ACR70 results showed a similar pattern. Response and remission rates were similar in pts with and without prior TNF inhibitor exposure in the CZP groups. However, response and remission rates at Wk 34 in the PBO group were considerably lower for pts with prior TNF inhibitor exposure compared to without, for example CDAI remission 6.9% vs. 22.5% and SDAI remission, 3.4% vs. 20.0%(Fig.). Conclusions: CZP demonstrated similar efficacy in RA pts with or without prior exposure to TNF inhibitors over 34 Wks. When CZP was withdrawn at Wk 16 in ACR20 responders, there appeared to be a greater maintenance of response in pts who had not previously been exposed to TNF inhibitors. References: Weinblatt et al. Ann Rheum Dis 2011;70(Suppl3):414 Disclosure of Interest: M. Schiff Grant/Research support from: UCB Pharma, Consultant for: UCB Pharma, O. Davies Employee of: UCB Pharma, B. Bennett Shareholder of: UCB Pharma, K. Luijtens Employee of: UCB Pharma, D. Furst Grant/Research support from: UCB Pharma, Consultant for: UCB Pharma, Speakers Bureau: UCB Pharma